Legal Protection for the First Certificate Holder Upon the Issuance of a Duplicate Certificate - Mubarok, Mohammad Ibnu; Riyanto, Taufan Fajar (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze the legal protection for the first certificate holder in the case of the issuance of duplicate certificates and to determine the factors causing the emergence of duplicate certificates and how the Supreme Court's legal considerations in Decision No. 189K/Pdt/2011. This type of research is normative juridical with a statutory, conceptual, and case approach. The results of the study indicate that the first certificate holder has strong legal protection and its position is recognized as more legitimate than subsequent certificates. The causes of the issuance of duplicate certificates include administrative errors, negligence, or unlawful acts. The Supreme Court's considerations in the decision emphasize that the first certificate must take precedence for legal certainty. Thus, legal protection for the first certificate holder is an important part of ensuring legal certainty in the Indonesian land system. Keywords: Certificates; Dual Certificates; Legal Certainty; Legal Protection.